Evaluasi Kinerja Sistem Isolasi Transformator Kertas Kraft Terendam Minyak Mineral Pada Sel Uji Penuaan Termal Dipercepat - Rahman Azis Prasojo; Kresna Bayu Priambodo; Anton Setya Aji Herdiansyah; Rohmanita Duanaputri; Slamet Nurhadi; Epiwardi (Elposys: Jurnal Sistem Kelistrikan, 2022)
The transformer insulation system in the form of oil-immersed paper, is the most important part of a transformer. This isolation system needs to be ensured that it has the appropriate characteristics, and is resistant to stress due to transformer operation. The most commonly used method for evaluating insulation life is the accelerated thermal aging test. Insulating oil-immersed paper is sealed in a vessel with a ratio in the Accelerated Thermal Aging Chamber with a volume capacity of 3600 ml. It takes about 3000 ml of oil to be poured into a tube with a ratio of insulating oil to insulating paper rolled on copper which is 10:1 and then heated in a thermal oven to accelerate aging. This study aims to develop an Accelerated Aging Chamber for evaluating the performance of transformer isolation systems. The developed test cell is able to reach a set-point of 150°C in 16 minutes with on/off control while PID control in 37 minutes with a Human Machine Interface for monitoring and collecting temperature data in real time, and maintaining that temperature until the end of the experimental period. Theresults of the sample will later be tested for the characteristics of the transformer insulation, namely tensile strength, color scale, andbreakdown voltage due to thermal stress.